Islamic Criminal Law Reform in Corruption Cases: Maqasid al-Shariah Perspective - Thamsir, Moh; Latif, Mukhtar; Muhammad, Pauzi (Jurnal Ius Constituendum, 2025)
This study aims to examine the reform of Islamic criminal law in addressing corruption cases through the lens of Maqasid al-Shariah (objectives of Islamic law). The urgency of this research lies in the systemic and pervasive nature of corruption, which undermines governance, public trust, and societal welfare, necessitating a legal framework that not only punishes but also prevents corruption in line with Islamic principles. Employing a normative juridical approach, this research analyzes primary and secondary legal materials related to corruption and Islamic law. The findings reveal that Maqasid al-Shariah provides a holistic framework that emphasizes prevention, rehabilitation, and justice, offering a balanced approach to corruption eradication. The novelty of this study lies in integrating Maqasid al-Shariah into Indonesia’s legal system to address corruption's root causes while promoting societal welfare and justice. Reforming Islamic criminal law based on Maqasid al-Shariah can strengthen anti-corruption efforts by focusing on justice, prevention, and societal welfare. This approach contributes to a more holistic and adaptive legal framework, supporting the eradication of corruption in Indonesia.